PENGEMBANGAN PEDOMAN PRAKTIKUM KIMIA BERBASIS INKUIRI UNTUK CALON GURU SEKOLAH DASAR - Pernanda Evangelista; Hairida Hairida; Muhammad Irfan Izudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Practical learning is an important part of chemistry learning because it can help students understand concepts more concretely through experimental activities. However, the chemistry practicum guidelines used in learning still tend to focus on proving concepts and therefore do not fully facilitate the process of active scientific inquiry. This condition causes the development of critical thinking, problem-solving, communication, and collaboration skills as part of 21st-century skills to not develop optimally. Therefore, it is necessary to develop inquiry-based chemistry practicum guidelines that can encourage students to carry out a systematic investigation process in practicum activities. This study aims to develop and test the feasibility of inquiry-based chemistry practicum guidelines for prospective elementary school teachers. The research method used is research and development (R&D), which includes the stages of needs analysis, product design, development, expert validation, and product revision. Validation was carried out by material experts and media experts to assess the feasibility of content, presentation, language, and graphics. The results of the study indicate that the developed inquiry-based chemistry practicum guidelines have a good level of feasibility and are suitable for use as learning resources in chemistry practicum activities for prospective elementary school teachers.